2017
DOI: 10.7705/biomedica.v38i0.3911
|View full text |Cite
|
Sign up to set email alerts
|

Impacto metabólico e inflamatorio de una comida rica en grasas saturadas y su relación con la obesidad abdominal

Abstract: Introduction: The postprandial stage is associated with the increase of markers related to cardiovascular risk, and its intensity depends on the metabolic state. Objective: To determine the impact of a high-fat meal intake on the metabolic and inflammatory profile, and its relationship to abdominal obesity. Materials and methods: This clinical trial included 42 individuals (21 with abdominal obesity). We measured glucose, insulin, lipid profile, reactive C protein, lipopolysaccharides, andinterleukin 6 in fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that ingestion of a meal high in saturated fat can induce metabolic endotoxemia [42,43] and increase the expression of proinflammatory immunoregulatory molecules such as lipopolysaccharides [42], TNFα, VCAM-1 [43] and IL-1β [44], as well as modulating circulating miRNAs controlling inflammatory and lipid and protein metabolism in the postprandial period [43], while increased unsaturated fatty acid consumption could attenuate the inflammatory status [44]. Intake of foods high in saturated fat was shown to postprandially influence blood lipid concentrations independently of body weight, and to more strongly influence glycaemic and proinflammatory lipopolysaccharides and metabolic risk [45].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ingestion of a meal high in saturated fat can induce metabolic endotoxemia [42,43] and increase the expression of proinflammatory immunoregulatory molecules such as lipopolysaccharides [42], TNFα, VCAM-1 [43] and IL-1β [44], as well as modulating circulating miRNAs controlling inflammatory and lipid and protein metabolism in the postprandial period [43], while increased unsaturated fatty acid consumption could attenuate the inflammatory status [44]. Intake of foods high in saturated fat was shown to postprandially influence blood lipid concentrations independently of body weight, and to more strongly influence glycaemic and proinflammatory lipopolysaccharides and metabolic risk [45].…”
Section: Introductionmentioning
confidence: 99%
“…This oil has a great nutritional potential with multiple health benefits, such as, strengthening the cardiovascular system, preventing heart disease [3] and maintaining brain health [4] Moreover, the set of sterols present in the oil shows a hypocholesterolemic and antioxidant effect [5].…”
Section: Introductionmentioning
confidence: 99%
“…This increased interest in the higher incidence of obesity has arisen because it is the main cause of non-communicable diseases such as type 2 diabetes mellitus, cardiovascular diseases, and some types of cancer, which in turn increase the mortality rate due to these diseases and generate a heavy economic burden on health systems worldwide [ 3 , 4 ]. Obesity involves a complex interaction between genetic and environmental factors, including diet [ 5 , 6 , 7 ]. The adoption of unhealthy lifestyles and the adherence to a typical Western dietary model, including a low level of physical activity, and the consumption of saturated fats, carbohydrates, and sugary beverages, constitutes the main cause of obesity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a rapid remodeling of the lipoproteins and a greater number of metabolic adaptations compared to the fasting state [ 9 ]. The problem arises because in modern life, people often consume foods more than three times a day, so they remain in the postprandial state for most of the day [ 5 , 10 ], without the opportunity to achieve lipid clearance or glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%